LABOR HARASSMENT FROM THE JURISPRUDENTIAL PERSPECTIVE OF THE COLOMBIAN CONSTITUTIONAL COURT - De los Ríos Castiblanco, Juan Carlos (2017)
In Colombia, Law 1010 is issued on January 23, 2006, with the «purpose of defining, preventing, correcting and punishing the various forms of aggression, mistreatment, disrespectful and offensive treatment and, in general, any outrage against human dignity» (Congress of the Republic, Law 1010, 2006). These concepts are framed within the Colombian Constitutional Jurisprudence, as rights that the State has the obligation to defend for being considered from  the  constitution of 1991 a Social State of law, where human dignity is one of the principles of Greater constitutional relevance.  It  is  then  written a tour of the relevant manifestations of the Constitutional Court from the critical analysis, trying to perceive the elements that could be considered evolutionary in the protection of workers, and others that not so much could be called «evolution».